Perancangan Situs Web Rumah Sakit Islam Masyithoh Bangil Dengan Mengadaptasi Human Centered Design - Septy Kusumaning Pratiwi; Agi Putra Kharisma; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Mashyithoh Islamic Hospital is one of the private hospitals located in Bangil District, Pasuruan Regency. Based on the results of interviews with the head of marketing division, Masyithoh Islamic Hospital requires media to be a means of delivering information services and facilities that are easily accessible by anyone at all as a media promotion of hospital products and services. According to the health minister rules RI chapters (3) of Article (3) of paragraph 1 and 2 explain that health care facilities can participate organizes advertising / publicity of health services through the media on the condition that must comply with the code of conduct hospital in Indonesia. In accordance with the rules and to achieve marketing objectives, one of the media that can be utilized is the use of the website. Website is used as a media that can be a liaison between the hospital and the community in terms of information delivery. In this research, the website design of Masyithoh Islamic Hospital by adapting Human Centered Design (HCD), because involving the stakeholders in the process. The prototype is then evaluated using the Focus Group Discussion (FGD) approach. From the evaluation result, the design improvement of prototype and then confirmed to RSI Masyithoh.